Assessment of Physicochemical Properties, Cytotoxicity, Antimicrobial Activity, and Flexural Strength of Self-Cured Acrylic Resin With Silver Nanoparticles on Delaminated Clay for Removable Appliances - Reza Mahmoudi Anzabi; Baharak Divband; Mustafa S. Tukmachi; Samin Vahedifar; Mahdiyeh Esmaeilzadeh; Fatemeh Yeganeh Sefidan; Morteza Jahanbani; Ali Rafighi (International Journal of Dentistry)
Conclusion: In conclusion, this study underscores the potential of PMMA modification with AgNPs-DC nanoparticles to confer satisfactory antibacterial and antifungal characteristics. Nonetheless, the cytotoxicity of the synthesized polymer increased with nanoparticle concentration and duration. Notably, ball milling proved effective in reducing nanoparticle aggregation.